Decay and continuous dependence estimates for harmonic vibrations of micropolar elastic cylinders - Aron, M.; Chirita, S. (Archives of Mechanics, 1997)
A principle of Saint-Venant-type is established for a right cylinder composed of an anisotropic, linear, homogeneous micropolar elastic solid and subjected to harmonic loading on one of its ends. The amplitude of the harmonic vibrations of this cylinder is also shown to depend continuously on the prescribed data.